Does the seed fall far from the tree? Weak fine-scale genetic structure in a continuous Scots pine population - Niskanen, Alina K.; Kujala, Sonja T.; Kärkkäinen, Katri; Savolainen, Outi; Pyhäjärvi, Tanja (Peer Community Journal)

(untitled)
Knowledge of fine-scale spatial genetic structure, i.e., the distribution of genetic diversity at short distances, is important in evolutionary research and in practical applications such as conservation and breeding programs. In trees, related individuals often grow close to each other due to limited seed and/or pollen dispersal. The extent of seed dispersal also limits the speed at which a tree species can spread to new areas. We studied the fine-scale spatial genetic structure of Scots pine (Pinus sylvestris) in two naturally regenerated sites located 20 km from each other in continuous south-eastern Finnish forest. We genotyped almost 500 adult trees for 150k SNPs using a custom made Affymetrix array. We detected some pairwise relatedness at short distances, but the average relatedness was low and decreased with increasing distance, as expected. Despite the clustering of related individuals, the sampling sites were not differentiated (FST = 0.0005). According to our results, Scots pine has a large neighborhood size (Nb = 1680–3210), but a relatively short gene dispersal distance (σg = 36.5–71.3 m). Knowledge of Scots pine fine-scale spatial genetic structure can be used to define suitable sampling distances for evolutionary studies and practical applications. Detailed empirical estimates of dispersal are necessary both in studying post-glacial recolonization and predicting the response of forest trees to climate change.